Diseño prototipo de escaparate para la boutique “Metro Fashion” de la ciudad de Loja - Sisalima Salinas, Lourdes Janina (2016)
The present work exposes a proposal of showcase prototype design for a boutique of the city of Loja, taking like reference to the Polish poster for their creative freedom that has inspired for the realization of the designs, with surreal images and striking colors, all this in order to present new options for the owner and the spectator